Radiosensitizers, radioprotectors, and radiation mitigators - Jayam Raviraj; Vijay Kumar Bokkasam; Venkata Suneel Kumar; Uday Shankar Reddy; Venkata Suman (Wolters Kluwer Medknow Publications, 2014)
Radiotherapy is regarded as one of the most important therapeutic modality for the treatment of malignant lesions. This field is undergoing rapid advancements in the recent times. With the use of radiosensitizers and radioprotective agents, the course of radiotherapy has improved the sensitization of tumor cells and protection of normal cells, respectively. The aim of this paper was to critically review and analyze the available compounds used as radiosensitizers, radioprotectors, and radiation mitigators. For reviewing, the author used the electronic search for the keywords 'Radiosensitizers', 'Radioprotectors', 'Radiation mitigators' on PubMed for inclusion of previously published articles and further search of reference papers on individual radiosensitizing and radioprotecting agents was done. Radiosensitizers are agents that sensitize the tumor cells to radiation. These compounds apparently promote fixation of the free radicals produced by radiation damage at the molecular level. The mechanism of action is similar to the oxygen effect, in which biochemical reactions in the damaged molecules prevent repair of the cellular radiation damage. Free radicals such as OH + are captured by the electron affinity of the radiosensitizers, rendering the molecules incapable of repair. Radioprotectors are compounds that are designed to reduce the damage in normal tissues caused by radiation. These compounds are often antioxidants and must be present before or at the time of radiation for effectiveness. Other agents, termed mitigators, may be used to minimize toxicity even after radiation has been delivered. This article tries to discuss the various aspects of radiosensitizers, radioprotectors, and radiation mitigators including the newer agents.